Flexible Rockfall Barriers Subjected to Extreme Loads - Volkwein, Axel; Roth, Andrea; Gerber, Werner; Vogel, Aron (Structural engineering international : journal of the International Association for Bridge and Structural Engineering (IABSE), 2009)
Flexible rockfall barriers are proven protection systems to mitigate the hazard of rocks falling on people and infrastructure. To assure that such systems are able to dynamically stop falling rocks in reality, several guidelines with full-scale tests were introduced worldwide. These guidelines consider very standardized and repeatable load cases but cannot take possible extreme loads into account. Two examples of extreme loads were investigated, high-speed rockfalls where the impact velocity is well above 25 m/s as described in the testing guidelines, and a tree trunk strike with the same weight as a falling rock but with a much smaller impact area. Finally, an overview of the performance of flexible barrier subject to dynamic area loads, such as debris flow, shallow landslides or snow avalanches is given.